The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00126-016-0675-7
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization and origin of low-T willemite (Zn2SiO4) mineralization: the case of the Bou Arhous deposit (High Atlas, Morocco)

Abstract: International audienceWillemite (Zn2SiO4) usually reported in hypogene non-sulfide deposits is described as the main ore mineral in the carbonate-hosted Bou Arhous zinc deposit. This deposit is located in the High Atlas intracontinental range that formed during the Tertiary. Based on a set of microscopic observations, it was possible to establish that willemite replaces primary sphalerite. On the basis of cathodoluminescence imaging, three successive generations of willemite are distinguished, with evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…Germanium incorporation in willemite is not unusual, having already been observed in various Zn-silicate deposits, e.g. Franklin (Sheffer, 1966), Tsumeb (Lombaard et al , 1986), Beltana (Groves et al , 2003), Bou Arhous (Choulet et al , 2017) and Tres Marias (Saini-Eidukat et al , 2009, 2016). In particular, Saini-Eidukat et al (2016) have described the structural occurrence of Ge in the Tres Marias willemite in detail, and have shown that “Ge in willemite occurs as Ge 4+ and is four-fold coordinated with oxygen, as expected because the ionic radius of Ge 4+ (0.44 Å) is close to that of Si 4+ (0.39 Å) and isomorphism of Ge 4+ with Si 4+ is most probable”.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Germanium incorporation in willemite is not unusual, having already been observed in various Zn-silicate deposits, e.g. Franklin (Sheffer, 1966), Tsumeb (Lombaard et al , 1986), Beltana (Groves et al , 2003), Bou Arhous (Choulet et al , 2017) and Tres Marias (Saini-Eidukat et al , 2009, 2016). In particular, Saini-Eidukat et al (2016) have described the structural occurrence of Ge in the Tres Marias willemite in detail, and have shown that “Ge in willemite occurs as Ge 4+ and is four-fold coordinated with oxygen, as expected because the ionic radius of Ge 4+ (0.44 Å) is close to that of Si 4+ (0.39 Å) and isomorphism of Ge 4+ with Si 4+ is most probable”.…”
Section: Discussionmentioning
confidence: 69%
“…Comparison of the δ 18 O compositions of the Kabwe willemite with willemites from other deposits of the world is hampered by lack of data. At present, δ 18 O compositions of willemite have been only measured at Sterling Hill (New Jersey, USA) (7.4–11.4‰ V-SMOW; Johnson et al 1990), at Vazante (Minas Gerais, Brazil) (10.9–13.8‰ V-SMOW; Monteiro et al , 1999), and at Bou Arhous (L'oriental Region, Morocco) (5.3–7.8‰ V-SMOW; Choulet et al , 2017), where willemite is considered to be precipitated from hydrothermal fluids (Johnson et al 1990; Monteiro et al , 1999; Choulet et al , 2017). Looking at the W1-water oxygen isotope fractionation curves, we see that for a limited range of temperatures only (~0 to 40°C), the precipitating fluids would be characterized by the negative or slightly positive δ 18 O compositions generally indicative of a relatively unaltered surface fluid origin in tropical latitudes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the mineralogy and origin of the non-sulfide ores have been neglected and have only recently become the subject of ongoing investigations [30][31][32].…”
Section: Introductionmentioning
confidence: 99%